Twin transitions & industry 4.0: unpacking the relationship between digital and green factors to determine green competitive advantage - Rehman, Shafique Ur; Giordino, Daniele; Zhang, Qingyu; Alam, Gazi Mahabubul (Elsevier Ltd, 2023)
The topic of twin transition is playing a key role within the current literature. There is also growing interest amongst researchers, managers, and policy makers to explore this phenomenon. This study investigates whether the pursuit of twin transition can enhance a company's green-based competitive advantage (CA). The authors conducted a PLS-SEM analysis to examine 459 responses collected through purposive technique. A regression analysis was used to further investigate the obtained data. Technological innovation is adopted as a mediator, whereas green work climate perception (GWCP) is adopted as a moderator. The findings suggest that IoT, green human resource management (HRM), and investment in environmental management strategies are directly and indirectly linked with a company's green CA. This study offers concrete suggestions on how the pursuit of environmentally-friendly and technological factors affect a company's green CA. This study makes the following contributions. First, technological innovation and green work climate perception increase green CA. Second, GWCP positively strengthens the relationship between technological innovation and green CA. The empirical findings suggest that management seeking to improve green CA can do so by adopting twin transition. This study further develops the literature on twin transition because it incorporates IoT, green HRM, investment in environmental management, technological innovation, and green work climate perception to measure green CA through the theoretical lens of natural resource-based view theory.